Identification of Proteins Related to Nickel Homeostasis in Helicobater pylori by Immobilized Metal Affinity Chromatography and Two-Dimensional Gel Electrophoresis. (27th November 2007) - Sun, Xuesong; Ge, Ruiguang; Chiu, Jen-Fu; Sun, Hongzhe; He, Qing-Yu
Abstract : Helicobacter pylori (H. pylori) is a widespread human pathogen causing peptic ulcers and chronic gastritis. Maintaining nickel homeostasis is crucial for the establishment of H. pylori infection in humans. We used immobilized-nickel affinity chromatography to isolate Ni-related proteins from H. pylori cell extracts. Two-dimensional gel electrophoresis and mass spectrometry were employed to separate and identify twenty two Ni-interacting proteins in H. pylori . These Ni-interacting proteins can be classified into several general functional categories, including cellular processes (HspA, HspB, TsaA, and NapA), enzymes (Urease, Fumarase, GuaB, Cad, PPase, and DmpI), membrane-associated proteins (OM jhp1427 and HpaA), iron storage protein (Pfr), and hypothetical proteins (HP0271, HP jhp0216, HP jhp0301, HP0721, HP0614, and HP jhp0118). The implication of these proteins in nickel homeostasis is discussed.